The EFFORTS TO IMPROVE THE CHEST PASS ABILITY OF GRADE V BASKETBALL ELEMENTARY SCHOOL RANDUSARI 02 - Budi Cahyono; Khafid Irkham (Ikatan Dosen Menulis, 2026)
This research was motivated by the low chest pass skills of fifth-grade students at Randusari 02 Elementary School in basketball. This study aimed to improve chest pass skills in basketball through the Wall pass Test game in fifth-grade students at Randusari 02 Elementary School. The research used Classroom Action Research (CAR) and was conducted in two cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. The subjects were 23 fifth-grade students at Randusari 02 Elementary School. Data collection techniques included observation, chest pass skills tests, and documentation. Data analysis used quantitative and qualitative descriptive analysis. The results showed that the Wall pass Test game can improve students' chest pass skills. In the pre-cycle phase, the average student score was 66, with a learning completion percentage of 21%. In cycle I, the average score increased to 74, with a completion percentage of 52%. Furthermore, in cycle II, the average score increased to 81, with a completion percentage of 86%. Furthermore, student activity and enthusiasm in participating in learning also increased with each cycle. Based on the research results, it can be concluded that the implementation of the Wall pass Test game is effective in improving the chest pass skills of fifth-grade students at SDN Randusari 02 in basketball. The Wall pass Test game can be used as an interesting, active, and enjoyable alternative to physical education (PJOK) learning to improve students' basic basketball skills.